PENYISIHAN ZAT WARNA CIRO-16 SERTA KINETIKANYA MENGGUNAKAN KOMBINASI PROSES KONTAK STABILISASI DAN ADSORPSI KARBON AKTIF JENIS GRANULAR - Sudarjanto, Gatut
Abstract<p align="justify Nowadays, synthetic dyes are more preferable than natural dyes due to their advantages. They have great variety of colours, constant dose, easy to use, and stable in light as well as during washing. Synthetic dyes are widely used in a number of indutrial processes, such as textile, paper printing, colour photography, food colouring and cosmetic industries. Inefficiency in dyeing process results in 10-50% of all dyestuff being directly lost to wastewater, which will ultimately find its way into the environment. The pollution will give rise to public complaints and restricts the downstream use of the water. Azo dyes (-N=N-) account for 60-70% of all dyestuffs and are the most common chromophore of reactive textile dyes. Reactive dyes have high solubility in the water and loss to wastewater in significant amount. Degradation of azo dyes under aerobic conditions is slow and insignificant, given that this reaction occurs by reduction of azo bond, a process that is linked to the activity of anaerobic microorganisms. Therefore, under anaerobic conditions, the azo linkage can be reduced to form aromatic amines or aromatic sulphonated that are colorless but are known to be toxic and carcinogenic, whereas aerobic conditions are more amenable to mineralisation. From this contradiction, the combination of anaerobic and aerobic is believed to be the best process to solve the problem. A few batch preliminary experiments were done before the main research was proceeded. Various substances were tried out as an other alternative microorganism-growth media because the minimum media and yeast extract (co-substrate), which was usually used in batch process, was not economic if operate in a continuous bioreactor. In the beginning, finding the substance that was able -to--support themicroorganisms to remove -colour in a relalivly short time, cheap and easy to obtain, and did not produce considerable presipitate. As the alternative substance was chosen, which we found the 'tempe' waste (fermented soya bean) with 10% (v/v) concentrate as alternate growth substance, we startes to determine the biomass growth rate in the system and study the COD removaL We also optimized initial dose of the activated carbon which will be added into the reactor, and the adsorption capacity of activated carbon used in this research by Freundlich isotherm test. In this research, decoloim7ation of synthetic dye fabricated named Colour Index Reactive Orange-16 (CIRO-16) in wastewater were examined in laboratory-scale research using mixed culture microorganism in continuous contact stabilization bioreactor combined with granular activated carbon as microorganism-growth supporting media. As the control, contribution of microorganism and activated carbon in dye decolourization were also observed respectively. Operation conditions were controlled as follows; the influent debit was 1.5 I/hr, detention time in contact tank was maintain around 1 hour, detention time in stabilization tank were changed amongst 2, 3, 4, 5, and 6 hours, sludge recirculation factor was 100%, activated carbon maintenance dose was 12.5%, and sludge age varies by 5, 8, 10, and 15 days. The result showed that the higher the removal efficiency the longer the detention time and sludge age system. The efficiency tends to decrease when the detention time of stabilization tank reaches 6 hours with sludge age 15 days. The stage is believed to be an endogenous phase. As a result, the optimum condition has the age sludge to be 10 days with detention time of stabilization tank 5 hours. Research results showed 80% removal of colour with 10 days of sludge age, 1-hour detention time in contact tank, and 5 hours detention time in stabilization tank Removal of colour using microorganism without activated carbon was 38%, whereas using activated carbon without microorganism gave 32% removal These figures were very much lower in compare with main research result. In this research, we also determined the removal of COD, N-NH4 , total phosphate that were between 60 - 85%, 33 - 76%, 30 - 62%, respectively. Kinetics parameters analysis showed Âµk= (0,7917-0,8673) mg/I, }is = (0,2943-0,1384) mg/I, Y),2082 grVSS/grCOD, Vmax carbon = 0,17161hour, Vmax colour = 0,1272/hour, and a = 3,40-7,25. his research also proved that the combination of attached and suspended growth system in biological reactor was also able to decolounize synthetic dye containing wastewater. It was also capable to increase activated carbon adsorption capacity used in the system through biogeneration process.